EDUKASI MELALUI MEDIA BUKU INTERAKTIF DIGITAL SELF-COMPASSION BERPENGARUH PENCEGAHAN KECEMASAN DAN DEPRESI REMAJA (Jurnal Kesehatan Siliwangi, 2023)
Background: Adolescents who are in their final year of high school experience several changes, seeking self-identity, social roles and life goals. However, not all teenagers can adapt, thereby increasing the potential for anxiety and depression. The highest proportion is in junior high and high school. The media to pour out their emotional is using a diary or an ordinary notebook. Based on the students's habits, the researchers interested in alternative health promotion media, namely the Self-Compassion interactive e-book. Objective: To know the effect of education through the Self-Compassion interactive e-book on adolescents knowledge about anxiety and depression prevention at SMAN 15 Bandung. Method: Pre-Experimental One Group Pretest-Posttest. Population 389 students. Sample amounted to 80 students in grade 11, SMAN 15 Bandung. Simple Random Sampling Technique. Data collection using the Self Compassion Scale instrument and measured by a knowledge scale. The media is developed using the PPE Model, with very valid,results from material experts and media experts. Data analysis with Wilcoxon Signed Rank Test. Results: The average knowledge before being given education is 55.38. The average knowledge after being given education is 78.86. The p value on the knowledge of before and after being given education is (p = 0.0001). Conclusion: There is a significant effect on students after being given education through the Self-Compassion interactive e-book on increasing adolescent knowledge of SMAN 15 Bandung.